The Role of AI in Transforming Healthcare Data - Srinivas Maddela (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Artificial Intelligence (AI) is increasingly becoming a key enabler in the transformation of healthcare systems globally. The healthcare industry, traditionally burdened with siloed, complex, and vast amounts of data, is now leveraging AI to enhance data analysis, improve decision-making, and optimize patient outcomes. By integrating machine learning, natural language processing, and deep learning technologies into healthcare data workflows, AI is unlocking new opportunities for predictive analytics, personalized medicine, and operational efficiencies. This paper explores the role of AI in transforming healthcare data, highlighting its applications, challenges, and future prospects in revolutionizing healthcare delivery and improving patient care.